2017
DOI: 10.25081/jmb.2017.v1.816
|View full text |Cite
|
Sign up to set email alerts
|

Biological screening of Ajuga iva extracts obtained by supercritical carbon dioxide and pressurized liquid extraction

Abstract: Extracts obtained by supercritical carbon dioxide extraction (SCE) and pressurized liquid extraction (PLE) from the Ajuga iva aerial parts growth in three different geographical sites of Alegria were analysed. Tocopherols in SCE Extracts were quantified by HPLC, α-tocopherol dominated the profile in both A. iva of Bejaia (BEJ) and Bordj Bou Arreridj (BBA), while β-tocopherol was the lowest. PLE method produced higher extraction yields than SCE method, which ranged from 0.31 to 24.95% (w/w), the water gave the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Therefore, from the obtained results for all extracts under study, the most suitable extractor solvents were water and ethanol. The obtained results are in accordance with those found by several studies (Bendif et al, 2017;El-lamey, 2022;Fettach et al, 2019;Makni et al, 2013;Salem et al, 2016;Senhaji et al, 2020). Bioactive compounds are synthesized in different structures and chemical natures which affect their extraction (Joana Gil-Chávez et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, from the obtained results for all extracts under study, the most suitable extractor solvents were water and ethanol. The obtained results are in accordance with those found by several studies (Bendif et al, 2017;El-lamey, 2022;Fettach et al, 2019;Makni et al, 2013;Salem et al, 2016;Senhaji et al, 2020). Bioactive compounds are synthesized in different structures and chemical natures which affect their extraction (Joana Gil-Chávez et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with several similar studies, which showed that aqueous extracts showed higher yields than extracts obtained by organic solvents [ 81 , 82 , 83 ]. For example, extraction yields determined from extracts of A. iva (L.) obtained by acetone, ethanol, and water were respectively around 2.3%, 2.6%, and 24% [ 19 ]. Additionally, the extraction yield seems to be influenced by the degree of polarity of the solvent, the extraction method, the extraction time, as well as by the degree of polarity of the various components of the extract, such as the phenolic constituents [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This plant species has a number of slang names, including Chendghoura and Toutoulba [ 18 ]. Some Ajuga species are regarded as weeds, yet many are employed in horticulture as ground or border cover and in rock gardens [ 19 ]. In Morocco, many ethno-medical uses have been reported for this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Makni et al [ 9 ] observed that the extraction yield of A. iva differed between methanol, aqueous, hexane, and chloroform extractions. Bendif et al [ 10 ] observed different concentrations of total phenolics and free radical-scavenging activity with different extraction methods (acetone, ethanol, and water) of A. iva .…”
Section: Introductionmentioning
confidence: 99%